(untitled) (Annals of Medical Research, 2021)
Aim: Poisoning from scorpion sting is an important public health problem, and may cause disability and death especially in childhood. In our study, we aimed to evaluate the sociodemographic characteristics, clinical findings, laboratory results and dynamic disulfide/thiol homeostasis as oxidative stress factor of pediatric patients presenting with scorpion sting complaints to our hospital.Material and Methods: Forty patients in the 0-18 age group who admitted to the Pediatric Emergency Outpatient Clinic due to scorpion sting intoxication were included in the patient group, and 38 healthy children in the same age group were included in the control group. Patients’ sociodemographic characteristics, clinical and laboratory findings, treatment modalities and the outcomes were examined. In addition, thiol/disulfide levels in the serums of patients were studied with a new method developed by Erel et al.Results: Forty pediatric patients (57.5% male and 42.5% female) presenting with scorpion sting complaints were included in the study. Results: There was no statistically significant difference among patient and control group with regards to the mean native thiol levels. While it was found that the levels of the total thiol, disulfide, disulfide/native thiol and disulfide/total thiol were statistically significant higher in the patient group, the native thiol/total thiol ratio was found to be lower at a significant level. Conclusion: The scorpion sting incidents are still an important health problem in Turkey. In children with scorpion sting, the thiol/disulfide homeostasis was observed to shift towards the disulfide side, i.e. to the right, indicating an increase in oxidative stress.